P-014 A Six-Sigma Approach for Decreasing Door To Needle Times In Endovascular Stroke Therapy. (29th July 2016) - Rai, A; Smith, M; Boo, S; Tarabishy, A; Hobbs, G; Carpenter, J
Abstract : Background and purpose: Delays in delivering endovascular stroke therapy adversely impact outcomes. Time-sensitive treatments such as stroke interventions benefit from methodically developed protocols. Clearly defined roles in these protocols allow for parallel processing of tasks resulting in consistent delivery of care. The paper presents the outcomes of a quality-improvement (QI) process directed at reducing stroke treatment times in a tertiary level academic medical center. Methods: A six-sigma based QI-process was developed over a 3 month period. After an initial analysis, procedures were implemented and fine-tuned to identify and address rate-limiting steps in the endovascular care pathway. Prospectively recorded treatment times were then compared in two groups of patients who were treated "Before" (n = 64) or "After" (n = 30) the QI-process. Three time intervals were measured: ER-arrival to CT-scan (ER-CT), CT-scan to interventional lab (CT-Lab) and Interventional lab arrival to groin puncture (Lab-puncture). The ER-CT time was 40(±29)-minutes in the "Before" and 26(±15)-minutes in the "After" group (p = 0.008). The CT-Lab time was 87(±47)-minutes in the "Before" and 51(±33)-minutes in the "After" group (p = 0.0002). The Lab-puncture time was 24(±11)-minutes in the "Before" and 15(±4)-minutes in the "After" group (p < 0.0001). The overall ER-arrival to groin-puncture time was reduced from 2 hours, 31 minutes (±51 minutes) in the "Before" to 1 hour, 33 minutes (±37 minutes) in the "After" group, (p < 0.0001). The improved times were observed for both during and off-hours interventions. Conclusion: A protocol driven process can significantly improve efficiency of care in the time-sensitive stroke interventions. Disclosures: A. Rai: 1; C; stryker Neurovascular. 2; C; stryker Neurovascular. M. Smith: None. S. Boo: None. A. Tarabishy: None. G. Hobbs: None. J. Carpenter: None.